Natural History of the Farm A Guide to the Practical Study of the Sources of Our Living in Wild Nature - Needham, James G. (Cornell University Press, 2019)
This is a guide to the practical study of the sources in wild nature of our living. It contains a series of study outlines for the entire year, and deals with both the plants and animals of the farm-the things that men have chosen to deal with as a means of livelihood and of personal satisfaction in all ages.